The Control problem discovery formula: Practical framework in MCS for research and business - Aris Surya Putra; Wiyono Pontjoharyo (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2025)
Purpose – This study develops a conceptual framework as a formula to systematically discover control problems within organizations by integrating organizational objectives, nature, and existing management control systems (MCS), so facilitating the solution process for research and business. Methods – This qualitative research uses six undergraduate students’ theses on MCS from diverse organizational contexts. It is based on information analysis from collected documentation through interviews, observations, and document analysis, completed with a triangulation method to minimize bias. Then, we do synthesis and exploration to construct an effective framework for discovering control problems. Findings – The study highlights that control problems often arise from misaligned objectives, organizational and cultural complexities, and deficiencies in MCS design and implementation. The proposed framework, as a formula, can connect organizational goals, nature, and MCS through iterative feedback loops, enabling organizations to discover root problems effectively and facilitate the solution development process. Implications – Practically, this framework provides an approach as a systematic formula and implemented in a structured way to help managers, researchers, and businessmen discover organizations’ control problems effectively. Originality – This research fills gaps in the MCS literature by offering a practical formula with mechanisms to demonstrate and explain the linkages between the symptoms of control problems and their root causes.